COVID-19: impact on the mental health of university students - Aswal, Priyanka; Singh, Parvesh (International Journal Of Community Medicine And Public Health, 2021)
Background: Ever since the outbreak of the covid-19 pandemic, education institutions in the entire country were shut down. This shutdown of universities caused the students to stay at home which caused a detrimental impact on their mental health. Methods: This survey-based study aims to decipher the impact the lockdown has caused on the mental well-being of the students. The survey was conducted through a set of online questionnaires. Results: The results of the study show that the students suffered from various psychological problems. Anxiety and stress were the most prevalent amongst mental illnesses and were reportedly increased due to uncertainty about future prospects like job and graduation. Conclusions: The study confirms that the pandemic has had a negative impact on the psychological health of the patients and has amplified stress and fear amongst them.